2015
DOI: 10.1159/000377637
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Drug-Drug Interaction of Losartan and Glimepiride in Rats and Its Possible Mechanism

Abstract: Background: Losartan and glimepiride are commonly used drugs to treat chronic diseases of hypertension and diabetes; they are both substrates of CYP2C9. The aim of the present study was to investigate the possible interaction of losartan and glimepiride both in vitro (rat liver microsomes) and in vivo (healthy Sprague-Dawley rats). Methods: In rat liver microsomes, 1-10 μmol/l losartan and glimepiride were coincubated, and the inhibitory effect was analyzed. In the subsequent pharmacokinetic study, 15 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Chen et al indicated that Glimepirea could increase the concentration levels of LOS and EXP3174 in the serum. The AUC 0-t of LOS was increased by 11.18%, which was lower than that of SMI ( Chen et al, 2015 ). The serum concentration of EXP3174 was associated with the degree of inhibition of CYP3A4 and CYP2C9 based on the fact that SMI could only inhibit the activity levels of the metabolic enzymes CYP3A4 and CYP2C9.…”
Section: Discussionmentioning
confidence: 72%
“…Chen et al indicated that Glimepirea could increase the concentration levels of LOS and EXP3174 in the serum. The AUC 0-t of LOS was increased by 11.18%, which was lower than that of SMI ( Chen et al, 2015 ). The serum concentration of EXP3174 was associated with the degree of inhibition of CYP3A4 and CYP2C9 based on the fact that SMI could only inhibit the activity levels of the metabolic enzymes CYP3A4 and CYP2C9.…”
Section: Discussionmentioning
confidence: 72%
“…The obvious medical interaction appeared by regulation of medical absorption, distribution, metabolism, and excretion with CYP450 as well as UDP-glucuronosyl transferase (UGT) and drug transport protein (OCT1, OCT2, OAT1, OAT3, OATP1B1, OATP1B3, P-gp, and BCRP) [ 19 ]. The binding rate of drug plasma protein was also the important factor to the interaction, especially to the approachable drug with plasma protein [ 21 ]. In addition, the constituent of Uncaria was complex; there were isorhynchophylline, corynoxeine, isocorynoxeine, corynantheine, corynoxein, isocorynoxeine, and so forth besides rhynchophylline [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%